2020
DOI: 10.1002/jsp2.1084
|View full text |Cite
|
Sign up to set email alerts
|

Comparing cellular bone matrices for posterolateral spinal fusion in a rat model

Abstract: IntroductionCellular bone matrices (CBM) are allograft products that provide three components essential to new bone formation: an osteoconductive scaffold, extracellular growth factors for cell proliferation and differentiation, and viable cells with osteogenic potential. This is an emerging technology being applied to augment spinal fusion procedures as an alternative to autografts.MethodsWe aim to compare the ability of six commercially‐available human CBMs (Trinity ELITE®, ViviGen®, Cellentra®, Osteocel® Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Autologous iliac cres bone graft (ICBG) remains the gold standard for spinal fusion, but its harvest is associated with long‐term donor site pain in up to 25% of patients 3 . A variety of alternative bone graft options are available (allograft, demineralized bone matrix, and cellular bone matrices), but none have proven to be suitable and effective substitutes for ICBG in the posterolateral spine 4,5 . Alternatively, biologic bone grafts substitutes such as bone morphogenetic protein (BMP) can be used either as an adjunct to autograft/allograft or it can be used as a standalone osteoinductive agent.…”
Section: Introductionmentioning
confidence: 99%
“…Autologous iliac cres bone graft (ICBG) remains the gold standard for spinal fusion, but its harvest is associated with long‐term donor site pain in up to 25% of patients 3 . A variety of alternative bone graft options are available (allograft, demineralized bone matrix, and cellular bone matrices), but none have proven to be suitable and effective substitutes for ICBG in the posterolateral spine 4,5 . Alternatively, biologic bone grafts substitutes such as bone morphogenetic protein (BMP) can be used either as an adjunct to autograft/allograft or it can be used as a standalone osteoinductive agent.…”
Section: Introductionmentioning
confidence: 99%
“…In the first study, 6 commercially available ACBMs (Trin-ity ELITE, ViviGen, Cellentra, Osteocel Pro, BIO 4 , and Map3) were compared with ICBG from syngeneic rats. 13 At 6 weeks, fusion rates by manual palpation were as follows: 5/15 in the ICBG group, 11/15 in the Cellentra group, 8/15 in the Trinity ELITE group, 2/15 in the Vivi-Gen group, and 0/15 in the Osteocel Pro, BIO 4 , and Map3 groups. Cellentra and Trinity ELITE also showed significantly greater bone volume increases than other implants (73% and 65%, respectively), seen on micro-CT as well as on histological analysis.…”
Section: Studies Comparing Acbm Productsmentioning
confidence: 93%
“…All human clinical studies and animal research in which ACBMs were used as bone substitutes or BGEs and where clinical and/or radiological outcome data were provided were included. The final 18 selected articles for the systematic review included 5 publications pertaining to animal research, [11][12][13][14][15] 5 publications pertaining to ACBM use in cervical spine surgery in human subjects, [16][17][18][19][20] and 8 publications pertaining to ACBM use in lumbar spine surgery in human subjects. [21][22][23][24][25][26][27][28] Tables 2 and 3 detail the study characteristics, patient profiles, and study outcomes for ACBM use in human clinical studies in cervical spine and lumbar spine surgery, respectively.…”
Section: Pubmed Search and Characteristics Of Selected Studiesmentioning
confidence: 99%
“…One recent study compared 6-week fusion outcomes of 6 commercially available human CBMs (Cellentra, Trinity, Vivi-Gen, Osteocel, map3, and Bio4) after use for augmenting spinal fusion in athymic rats. 48 Analysis of microCT performed in 15 euthanized animals revealed stable fusion in 11, 8, 2, 0, 0, and 0 for the 6 CBM products, respectively. 48 The authors concluded that the Trinity and Cellentra products achieved significantly better fusion rates in this particular animal model.…”
Section: Current Limitations To Implementation Of Cbmsmentioning
confidence: 94%